A portable x-ray fluorescence (pXRF) elemental dataset collected from Cambrian-age sandstone aquifer material, Wisconsin, U.S.A. - James J. Zambito, IV; Lisa D. Haas; Michael J. Parsen (Data in Brief, 2022)
This article provides a portable x-ray fluorescence (pXRF) elemental dataset from samples collected from a Cambrian Sandstone Aquifer in West-Central Wisconsin, U.S.A. Analyses were performed on drill core samples and well cutting materials collected using a variety of drilling methods. Elements presented in this dataset include aluminum (Al), arsenic (As), calcium (Ca), cobalt (Co), chromium (Cr), copper (Cu), iron (Fe), potassium (K), magnesium (Mg), manganese (Mn), molybdenum (Mo), nickel (Ni), phosphorus (P), lead (Pb), sulfur (S), silicon (Si), strontium (Sr), uranium (U), vanadium (V), and zinc (Zn). The accuracy and precision of the pXRF analyses was calculated based on repeated measurement of standards of similar lithology to the aquifer. This dataset could be used for 1) chemostratigraphy, 2) refinement of subsurface geochemical sampling techniques; 3) preventing or mitigating naturally-occurring groundwater trace metal contaminants in groundwater in the Upper Mississippi River Valley, and 4) evaluating impacts of regional industrial sand mining on aquifer geochemistry. The data presented in this article was used to select a subset of samples that represented the elemental variability within the overall aquifer succession for further geochemical and mineralogical analysis presented in the article entitled “Identifying the Source of Groundwater Contaminants in West-Central Wisconsin, U.S.A.: Geochemical and Mineralogical Characterization of the Cambrian Sandstone Aquifer” (Zambito et al., 2022).